2019
DOI: 10.3892/mmr.2019.9975
|View full text |Cite
|
Sign up to set email alerts
|

NEMO‑binding domain peptide ameliorates inflammatory bone destruction in a Staphylococcus�aureus‑induced chronic osteomyelitis model

Abstract: Osteomyelitis, which is characterized by progressive inflammatory bone destruction and resorption, is a difficult-to-treat infection. Staphylococcus aureus (S. aureus) is one of the major causes of this disease. This pathogenic microorganism possesses several characteristics, which facilitate its involvement in the occurrence and progression of osteomyelitis. A cell-permeable peptide inhibitor of the IκB kinase complex, the nuclear factor (NF)-κB essential modulator-binding domain (NBD) peptide, has been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Chronic osteomyelitis (COM) is a chronic bone infection characterized by progressive osteonecrosis and dead bone formation, which is closely related to the persistent infectious inflammation after infection (1). A variety of studies have shown that COM patients have disordered T lymphocyte proliferation, and clinical and animal studies also reveal that IL-2 expression and CD4+CD25+Foxp3 Treg cells increase in the peripheral blood in case of COM.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic osteomyelitis (COM) is a chronic bone infection characterized by progressive osteonecrosis and dead bone formation, which is closely related to the persistent infectious inflammation after infection (1). A variety of studies have shown that COM patients have disordered T lymphocyte proliferation, and clinical and animal studies also reveal that IL-2 expression and CD4+CD25+Foxp3 Treg cells increase in the peripheral blood in case of COM.…”
Section: Introductionmentioning
confidence: 99%
“…NBD peptides have been reported to modulate inflammation and osteoclastogenesis. 29 , 34 Based on our previous study, NBD peptides also promoted osteoblast differentiation impaired by TNFα. A possible underlying mechanism is that NBD peptides selectively attenuate the activation of NFκB by targeting NEMO and further abrogate (at least partly) the inhibitory effect of inflammation on osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 93%
“…Osteomyelitis is an acute or chronic infection of the bone characterized by suppurative inflammation, abnormal bone remodeling, and uncontrolled bone defects. 34 Antibiotic selection is still considered a difficult cure for osteomyelitis, although the risks of adverse reactions due to prolonged and widespread use of antibiotics have been discussed. S. aureus is the most common cause of bone infection.…”
Section: Discussionmentioning
confidence: 99%
“…Historically and currently, the most utilized models are long bone models, including tibial ( 115 121 ), femoral ( 49 , 122 124 ), and radial ( 125 129 ). Alternative models such as joint prostheses ( 130 , 131 ), mandibular defects ( 132 ), vertebral models ( 133 136 ) and implant infection via hematogenous seeding ( 137 ) exist. Induction of osteomyelitis among these various models can be accomplished via mechanical trauma, either defect ( 117 ) or fracture ( 49 ) creation and bacterial contamination with or without application of a sclerosing agent or foreign body placement ( 115 ), or through placement of contaminated implants ( 49 , 129 ).…”
Section: Small Animal Modelsmentioning
confidence: 99%